The role of gestures in predicting treatment outcomes in children with autism spectrum disorder - YE Qianying, LIU Linru, XU Yanting, ZHU Huilin, DENG Hongzhu (Xin yixue)
Objective To explore the role of gestures in predicting the treatment outcomes of early behavioral interventions in preschool children with autism spectrum disorder（ASD） across the dimensions of quantity， communicative function and integration ability of gestures. Methods Twenty-four ASD children who received early behavioral interventions for three months from March 2018 to March 2019 were recruited in this study in Child Development and Behavior Center of the Third Affiliated Hospital of Sun Yat-sen University. Before and after the interventions， a semi-structured interactive play paradigm was adopted to assess the gestures of ASD children. The social ability， adaptive behavior， and language expression of ASD children were evaluated by using the Adaptive Behavior Assessment System versionⅡ （ABAS-Ⅱ） and the Chinese Communication Development Inventory （CDI）. Multiple linear regression analysis was applied to predict the therapeutic effect by gestures in children with ASD. Results By comparing the ABAS-Ⅱ social skills domain （t=-5.850， P < 0.001）， conceptual skills domain （t=-5.548， P < 0.001）， practical skills domain （Z = -4.045， P < 0.001） and the total score （t = -6.771， P < 0.001）， as well as the CDI total score （Z = -3.263， P = 0.001）， the post-intervention scores of ASD children were significantly higher than their pre-intervention scores. Multiple linear regression model found that the frequency of eye gaze-integrated gestures before interventions in ASD children could predict the changes in the score of the social skills domain of the ABASⅡ （B = 1.565， P < 0.001） and the total score of the ABASⅡ （B = 7.331， P = 0.002）. Additionally， the total gesture frequency before interventions could predict the changes in the total score of the CDI （B = 17.089， P = 0.003）. Conclusions The ability to integrate gestures with eye gaze may predict the improvement in social skills and adaptive behavior after the interventions. The quantity of gestures could be an important predictor of progress in expressive language.